Cluster observations of plasma in the high latitude magnetotail associated with cuspaligned arcs - Mooney,MK; Milan,SE; Lester,M; Dandouras,I; Carr,C; Fazakerley,AN (Journal of Geophysical Research: Space Physics, 2025)
During periods of northward interplanetary magnetic field (IMF), the magnetospheric structureand dynamics are dramatically different compared to the southward IMF case. Previous studies using bothobservations and simulations have shown that under northward IMF the magnetotail becomes dominated byclosed magnetic flux and associated trapped particle populations. In this study, we analyze three intervals ofplasma observed in the high latitude magnetotail during a period of prolonged northward IMF, coinciding withobservations of cuspaligned arcs in the polar region. We observe that the plasma is typically observed by all 4Cluster spacecraft near simultaneously and has some substructure observed on length scales of 0.5–1.5 RE. Theplasma characteristics in each of the three intervals studied are similar. The ion and electron densities are on theorder of 10− 1–100 cm− 3. The electron energies typically vary between 102 and 103 eV. The ion energies arehigher compared to the electron energies and range between 102 and 104 eV. The ion temperatures are on theorder of 5–18 MK. The speed of the plasma crossing the Cluster spacecraft is between 1 and 10 kms− 1. In oneinterval Cluster observes distinctly different but adjacent plasma populations. We suggest these plasmapopulations are on interleaving flux tubes and may present supporting evidence for dual lobe reconnectionacting to trap plasma within the magnetosphere and resulting cuspaligned arc formation